An efficient synthetic route to accelerate zeolite synthesis via radicals. Issue 9 (10th July 2018) - Cheng, Peng; Feng, Guodong; Sun, Chang; Xu, Wenjing; Su, Ji-Hu; Yan, Wenfu; Yu, Jihong
Abstract : A highly efficient radical-route is developed to accelerate the synthesis of zeolites via sodium persulfate by generating hydroxyl radicals. Abstract : The energy-efficient and green synthesis of zeolites that are highly demanded in the chemical industry has been a focus for decades. Here we report a highly efficient radical-route to accelerate the synthesis of zeolites via using sodium persulfate (denoted as SPS) as an additive in the hydrothermal reaction system of SiO2 –TPAOH–H2 O. The hydrothermal synthesis of highly crystalline silicalite-1 was shortened to 16 h from 24 h in the presence of 0.02 M SPS. Electron paramagnetic resonance (EPR) was used to characterize the radical species induced by SPS. More importantly, as compared with the conventional synthetic system, highly crystalline silicalite-1 can be synthesized with only half of the amount of organic structure-directing agents in the presence of SPS. With this route, we can not only speed up the hydrothermal crystallization of a silicalite-1 zeolite but also greatly reduce the usage of organic structure-directing agents. This radical-route demonstrates an efficient and green route for the synthesis of zeolites.